Security-reliability tradeoff scheme for cognitive relay networks with eavesdropping attack over Nakagami-m fading channels - Xingpeng WANG; Xiaorong XU; Andi HU; Wei FENG (Dianxin kexue)
Physical layer security (PLS) and reliability tradeoff scheme in a cognitive decode-and-forward (DF) relay network consisting of one source,one destination and multiple relays was investigated.A best relay selection scheme (BRS) against eavesdropping attack was proposed,in order to guarantee the maximum secure main link channel capacity.Traditional direct transmission scheme was taken into consideration as a benchmark.In addition,security-reliability tradeoff (SRT) performance was presented.Numerical results show that the proposed SRT scheme strictly outperforms traditional direct transmissions in terms of SRT performance.SRT performance can be enhanced obviously with the increasing of relays and Nakagami channel fading factor m for a given numbers of relays.